2017
DOI: 10.1016/j.msec.2017.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Impact of silica nanoparticle surface chemistry on protein corona formation and consequential interactions with biological cells

Abstract: functionalization is often used to improve NP biocompatibility or to enhance cellular uptake. But in biological media, the formation of a protein corona adds a level of complexity. The aim of this study was to investigate in vitro the influence of NP surface functionalization on their cellular uptake and the biological response induced. 50nm fluorescent silica NP were functionalized either with amine or carboxylic groups, in presence or in absence of polyethylene glycol (PEG). NP were incubated with macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 51 publications
7
56
0
1
Order By: Relevance
“…The nature of the coating, including resulting charge, surface chemistry and particle hydrodynamic size, influences the adsorption of proteins on the surface of nanoparticles: the protein corona [43,44]. For example, we demonstrated that bare silica beads covered by either a gold or a titanium oxide layer have different preferential binding to proteins [43].…”
Section: Importance Of the Protein Corona On Biological Interactions mentioning
confidence: 91%
“…The nature of the coating, including resulting charge, surface chemistry and particle hydrodynamic size, influences the adsorption of proteins on the surface of nanoparticles: the protein corona [43,44]. For example, we demonstrated that bare silica beads covered by either a gold or a titanium oxide layer have different preferential binding to proteins [43].…”
Section: Importance Of the Protein Corona On Biological Interactions mentioning
confidence: 91%
“…Silica nanoparticles (SiNPs) are one of the most widely used engineered nanomaterials. SiNPs with favorable properties (biocompatibility and biodegradability) have been widely exploited in the cosmetics, food, and pharmaceutical industries and in the biomedical fields [15][16][17][18]. With the widespread prevalence of SiNPs, potential dermal, oral, or intranasal exposure chances have increased.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the uptake level that is affected by surface charge may vary with cell type. For example, positively charged silica NPs (20, 30, 50, 80 nm) are more likely to be endocytosed than their pristine or negatively charged counterparts in A549 cells (Ojea-Jiménez et al, 2016); however, in RAW264.7 cells, 50 nm silica NPs with either a positive or a negative charge exhibited similar uptake levels (Kurtz-Chalot et al, 2017). In HepG2 cells, the cellular uptake of positively charged 3-aminopropyltrimethoxysilane (APTES)-ZnO NPs (10-30 nm) was greater than the uptake of pristine ZnO NPs (Bartczak et al, 2015).…”
Section: Surface Chargementioning
confidence: 98%
“…Regarding charged NPs, positive and negative charges exhibit different protein binding capacities. For example, silica NPs (50 nm) decorated with amine or carboxyl groups exhibited different protein binding levels, with the negatively charged silica NPs adsorbing more proteins from human serum than were adsorbed by their positively charged counterparts (Kurtz-Chalot et al, 2017). In another study, it was also found that polystyrene (PS) NPs (140 nm) decorated with carboxyl or amine group exhibited different binding capacities to human serum protein.…”
Section: Surface Chargementioning
confidence: 99%
See 1 more Smart Citation